Role of a surface hydroxyl group depending on growth temperature in atomic layer deposition of ternary oxides - Lee, Sanghun; Seo, Seunggi; Lee, Woo Jae; Noh, Wontae; Kwon, Se Hun; Oh, Il Kwon; Kim, Hyungjun (Journal of Vacuum Science and Technology A: Vacuum, Surfaces and Films, 2023)
Atomic layer deposition (ALD) of multicomponent materials is challenging because the growth characteristics often deviate from what is expected due to the difference in surface characteristics of heterogeneous and single materials, resulting in undesired thickness or properties. For metal oxides, the growth characteristics highly rely on the surface hydroxyl groups, which play a role as the reactive site. Thus, studying the reaction mechanism of a precursor on hydroxyl-terminated heterogeneous surfaces is important for understanding the nonideal growth of ternary oxide. Here, we investigated the correlation between hydroxyl and the growth of ALD TiSiOx depending on temperature, analyzing infrared spectra, and chemical compositions. The results show that large amounts of hydroxyl are detected in TiSiOx deposited at 100 °C, where the adsorption of H2O on Ti-O-Si bonds is favorable. It leads to higher growth per cycle (GPC) than the estimated value. In contrast, the hydroxyl disappears at 200 °C due to dehydroxylation, resulting in lower GPC. Differences in hydroxyl also influence the film density as revealed in x-ray reflection spectra, which is related to the film qualities (e.g., elastic modulus and dry etch rates). This work provides insight into how to control hydroxyl in the ALD of ternary oxides, which is susceptible to hydroxyl incorporation, leading to undesired growth characteristics.
Keywords: Atomic-layer deposition; Growth characteristic; Growth per cycle; Metal-oxide; Multicomponent materials; Property; Reactive site; Surface characteristics; Surface hydroxyl groups; Ternary oxides